Group identity and leading-by-example - Michalis Drouvelis; Daniele Nosenzo (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2012)
We study the interplay between leading-by-example and group identity in a public goods game experiment. A common identity between the leader and her followers is beneficial for cooperation: average contributions are more than 30% higher than in a treatment where no identity was induced. In two further treatments we study the effects of heterogeneous identities. We find no effect on cooperation when only part of the followers share the leader's identity, or when followers share a common identity that differs from that of the leader. We conclude that group identity is an effective but fragile instrument to promote cooperation.
Keywords: C92; D03; H41; 330; leading-by-example; leadership; public goods; voluntary contributions; cooperation; identity; experiment